O09.7 Knowledge, attitudes, and beliefs about hiv pre-exposure prophylaxis among u.s. army health care providers. (8th July 2017) - Garges, Eric; Blayock, Jason; Li, Yuanzhang; Wood, Shannon; Okulicz, Jason; Beckett, Charmagne; Murray, Clinton; Michael, Nelson; Scott, Paul; Hakre, Shilpa
Abstract : Introduction: Pre-exposure prophylaxis (PrEP) has become a promising modality in the global fight against HIV. No data is available about the current utilisation, knowledge, or attitudes about PrEP provision in the US Army. Recent analysis of HIV-infected Army personnel indicates men who have sex with men are most at risk. We conducted a survey to characterise the level of PrEP awareness and adoption and examine PrEP-related knowledge, attitudes, and beliefs associated with PrEP adoption. Methods: In October 2016 we initiated an online survey to eligible US Army healthcare providers in the fields of infectious disease, public health, internal medicine, family medicine, and flight medicine. Demographic and clinical practice data was collected as well as questions about PrEP knowledge, attitudes, and program implementation within the Army. Provider knowledge and attitudes were assessed in univariate and bivariate analysis. Results: 754 providers responded, largely from family medicine (58%) and internal medicine (18%) specialties. While a large proportion (31%) had been questioned by patients about PrEP, only 12% reported having prescribed it. Current experience with PrEP was highest (83%) among infectious disease providers. Concerns for widespread use included medication adverse effects (61%), compliance (56%), and a need for "more clear evidence" (54%), among others. While most (91%) endorsed the use of PrEP, and favoured the implementation of PrEP programs for service members at high risk, over half (54%) reported their knowledge of PrEP as 'poor'. Self-reported PrEP knowledge was associated with prior use of HIV antiretrovirals (p<0.0001). Almost half (43%) of providers surveyed felt that they had patients who would benefit from PrEP and a majority (83%) thought PrEP should be offered. Conclusion: There is widespread support and interest in US Army PrEP programs, however, self-reported knowledge is low. Successful PrEP implementation will require education and training of the healthcare provider workforce to improve knowledge and mitigate concerns about PrEP.